The Riverside anthology of literature - Hunt, Douglas (Boston Houghton Mifflin Company, 1988)
"The Riverside Anthology of Literature principally aims to be a book that gives students the tools to develop independent judgments, tastes, and enthusiasms about literature."
Includes indexes.
English text.